EVALUATION OF ECOLOGICAL SITUATION IN CASE OF ACCIDENTS ON TOWNSHIP ROADS - Rusakova, T. I. (Science and Transport Progress, 2015)
Purpose. The paper examines the question of creation a mathematical apparatus for estimation the ecological situation in case of accidents on township roads (explosions). First of all the development of numerical model to calculate the level of air pollution in the emission of toxic chemical, taking into account meteorological parameters of the environment. Identifying areas where the maximum allowable concentration of this pollutant (in this case, ammonia) is exceeded and favorable areas for the population.Methodology. The developed method of numerical calculation of the air pollution concentration in case of toxic chemical (ammonia) was used, which is based on the coordinated decision of the hydrodynamic task and task of the pollutants transfer in the atmosphere. Hydrodynamic solution is based on the method of discrete vortices with the different geometry of buildings and their relative position, and solution of the task about transfer the pollutant is based on convection-diffusion equation of pollutant transfer using implicit difference schemes.Findings. Several computational experiments were made on the base of the developed numerical model.As a result of the calculations the vortex structures were obtained, which are formed in the flow around buildings; the velocity field of the wind flow around buildings and picture of the streamlines in the flow were come out; the concentration of the toxic chemical (ammonia) in research domain was calculated; the comparative analysis with the maximum permissible concentration (MPC) for this pollutant were made; the regularities of changing the ammonia concentration from different sides of the building were determined. Originality. A numerical model that allows visually reconstructing and analyzing the flow pattern, the presence of dead zones, areas of reverse flow at different geometry of buildings and their relative position that influences the distribution of pollutant in the atmosphere was calculated.Practical value. The obtained results will allow evaluating the level toxic shock to persons in case of accidents (explosions) on township roads with taking into account the influence of the buildings geometry on the hydrodynamic flow structure and dispersion of pollution.